2012
DOI: 10.3233/ch-2011-1430
|View full text |Cite
|
Sign up to set email alerts
|

Following-up hemorheological consequences of gonadectomy in male and female rats

Abstract: Growing number of clinical and experimental data reflect to the gender differences of hemorheological parameters. However, little is known about the potential hemorheological effect of gonadectomy and consequent changes in sex hormone concentration. Adult, sameaged male and female rats were involved in the study. In control male and female group no surgical intervention was performed. In gonadectomized (GoE) male and female groups bilateral orchidectomy or ovariectomy were completed. Body weight measurement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Growing number of data underline the importance of hemorheological gender differences not only in the clinical investigations but also in the experimental medicine [32]. Furthermore, gonadectomy may additionally influence these micro-rheological gender differences, reflecting the influence of sex hormones, too [33]. The protective effect of estrogen has been demonstrated in numerous I/R studies including acute [47] and chronic hind limb [23], myocardial [10,27,30,37,52], brain [15,41] and intestinal ischemia [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Growing number of data underline the importance of hemorheological gender differences not only in the clinical investigations but also in the experimental medicine [32]. Furthermore, gonadectomy may additionally influence these micro-rheological gender differences, reflecting the influence of sex hormones, too [33]. The protective effect of estrogen has been demonstrated in numerous I/R studies including acute [47] and chronic hind limb [23], myocardial [10,27,30,37,52], brain [15,41] and intestinal ischemia [48].…”
Section: Discussionmentioning
confidence: 99%
“…The general anesthesia was provided by intraperitoneal administration of Thiopenthal ® (60 mg/kg). [33] the same protocol was completed as in I/R groups.…”
Section: Operative Techniques and Sampling Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The hematological and hemorheological parameters show differences depending on gender, hormonal status, and menstrual cycle [ 8 , 9 , 10 ]. Guillet et al found that during menstruation, the red blood cell deformability is decreased in the pre-ovulation and post-ovulation phases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only a few studies compared the gender-related responses of microrheological parameters in I/R injuries. [14][15][16][17] The aim of our study was to investigate the effects of intestinal I/R on systemic hemorheological parameters in a rat model. We hypothesized that during intestinal ischemia, the microrheological parameters of the blood worsen, and the degree of these changes differs in male and female, young and older rats.…”
Section: Introductionmentioning
confidence: 99%